An excitation coil layout method for improving the sensitivity of a rosette flexible eddy current array sensor. (2nd December 2019) - Fan, Xianghong; Chen, Tao; He, Yuting; Du, Jinqiang; Ma, Binlin; Song, Yujian
Abstract: Flexible eddy current array sensor has the characteristics of flexibility, light weight and convenient installation, and has great application prospects in metal structure crack monitoring. In allusion to the low sensitivity of traditional rosette flexible eddy current array sensor to crack identification, a co-directional excitation coil layout method is proposed, which significantly improves the sensitivity of sensor to crack identification . Firstly, by establishing the finite element model, the sensitivity of three sensing coils of the traditional sensor to crack identification is calculated to be 4.1%, 1.7% and 3.5%, respectively. The conclusion that the disturbed backflow between the excitation coils affects the sensitivity of each sensing coil to crack identification is obtained. In order to improve the sensitivity of the sensor, a new type of sensor using the co-directional excitation layout is proposed by changing the layout of the excitation coil. The simulation results show that the sensitivity of three sensing coils to crack identification is increased by 11.2, 43.1 and 36.0 times, respectively. Then, the sensitivity tests of the two sensors are carried out. The experimental results show that the sensitivity of three sensing coils of the sensor adopted co-directional excitation layout increases sequentially, which is 8.9, 23.7 and 13.3 times higher than the traditional sensor, indicating that the sensor adopted co-directional excitation layout is more sensitive to crack identification. Finally, the error analysis shows that the difference between the sensitivity of experimental results and simulation results is caused by the difference of lift-off. The research results privide an important way to improve the sensitivity of crack identification.